Corporate Governance and the Legal Environment: Some Theoretical Insights and Related UAE Evidence - Khan, Yousuf; D‘Silva, Kenneth E (Ushus Journal of Business Management, 2017)
Corporate Governance (CG) is complex. It has several strands and dimensions and has been much researched. Such research confirms that while ―trust‖ is fundamental to CG, the legal environment figures prominently within it. Within that environment, corporate law provisions often place a fiduciary (trusting) duty-obligation on directors to act in the best interests of the firm and stakeholders. Such provisions tend to be enshrined within three recurring principles, Probity, Accountability and Transparency, and designed to engender, support and encourage trust amongst all concerned. While extant country-specific corporate laws-rules-regulations prevail, additionally, CG matters are often realised via a voluntary (comply or explain) code. To that extent, such codes are part of the legal environment. Thus, a key objective of the paper is to assess, within the UAE context, the extent of any commonality or sharing of the above